2016
DOI: 10.4314/bajopas.v9i1.24
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant growth regulators on callus initiation in wormwood (<i>Artemisia annua</i> L.)

Abstract: Studies were carried out in the Biotechnology laboratory of Plant Science Department of Ahmadu Bello University Zaria, Nigeria to study the effect of some plant growth regulators on the in vitro initiation of callus using the leaves of Chiyong variety of Artemisia annua. The explants were sterilized and incubated on Murashige and Skoog basal media augmented with varying concentrations ranging from 0.5 to 3.0 µm/l of Giberellic acid (GA3), Benzyle amino purine (BAP), Naphthyle acetic acid (NAA),2,4-Dichlrophyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Tahir et al (2016) showed that an ideal plant growth hormone combination for callus formation in Artemisia annua was 0.5µM/L of both 6-benzylaminopurine and Naphthalene Acetic acid [62], similar to results obtained by Yuliani et al (2018) [58] although similar results were obtained by other workers with higher concentrations of BAP and different auxins [63].…”
Section: Callus Culture For Antimalarial Compoundssupporting
confidence: 69%
“…Tahir et al (2016) showed that an ideal plant growth hormone combination for callus formation in Artemisia annua was 0.5µM/L of both 6-benzylaminopurine and Naphthalene Acetic acid [62], similar to results obtained by Yuliani et al (2018) [58] although similar results were obtained by other workers with higher concentrations of BAP and different auxins [63].…”
Section: Callus Culture For Antimalarial Compoundssupporting
confidence: 69%
“…The endogenous level of GA 3 synthesized by the amaranth and C. gynandra seedlings might not be enough; therefore, exogenous application of GA 3 might have increased the growth of seedlings (Gurung et al, 2014). The maximum shoot length recorded in seeds of amaranth and C. gynandra treated with 500 ppm GA 3 might be attributed to the effect that GA 3 stimulates early growth of plants by improving cell division in the apical meristem (Tahir et al, 2014). Tahir and Mathew (2021) reported that GA 3 was used in the shoot proliferation media to increase shoot elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum shoot length recorded in seeds of amaranth and C . gynandra treated with 500 ppm GA 3 might be attributed to the effect that GA 3 stimulates early growth of plants by improving cell division in the apical meristem (Tahir et al., 2014). Tahir and Mathew (2021) reported that GA 3 was used in the shoot proliferation media to increase shoot elongation.…”
Section: Discussionmentioning
confidence: 99%